THE SECRET GARDEN - Burnett, Frances Hodgson, 1849-1924.; O'Flaherty, David Desmond; Petra Hanzak (Singapore : WS Education : Zenbooks JSC, 2024)
When young Mary Lennox suddenly loses her parents, she moves into her uncle's manor. Lonely and sad, the only comfort Mary has is exploring the manor's grounds. Then, she discovers an old, abandoned garden. With two unexpected friends, Mary gets to work. Is everything in the garden dead, or can Mary bring it back to life?
Keywords: Orphans -- Fiction; People with disabilities -- Fiction; Gardens -- Fiction; Children's stories, English